Effect of Piper betle L. and Rice Washing Water on Histamine-Forming Bacteria and Histamine in Indian Mackerel under Tropical Conditions - Kurnia Kusumawati; Rori Theresia; Alexia Lintang Putri Chandrakirana (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Indian mackerel (Rastrelliger kanagurta) is highly susceptible to histamine accumulation under tropical ambient storage due to histamine-forming bacteria (HFB). This study evaluated the temporal profile of HFB growth and its correlation with histamine levels in mackerel treated with Piper betle leaf extract and rice washing water. A completely randomized design with five treatments was applied: negative control, positive control, and combinations of Piper betle extract with rice washing water at ratios of 1:1, 1:3, and 1:5 (v/v). HFB populations were enumerated at 0, 6, 12, 18, and 24 hours using Niven's agar, while histamine concentrations were quantified spectrofluorometrically at 0 and 12 hours. Results showed that the 1:3 ratio treatment produced the lowest histamine level (61.11 mg/100g), suggesting enzymatic inhibition rather than merely bactericidal action. A bell-shaped dose-response relationship was observed, indicating pro-oxidant effects at excessive concentrations. The positive control exceeded the SNI limit of 100 mg/kg. This study concludes that the 1:3 combination of Piper betle extract and rice washing water has potential as a low-cost natural preservative for small-scale fisheries in tropical regions.